ANALISIS TIPE SOSIALISASI POLITIK PEMILIH PEMULA DI KELURAHAN PALAS KECAMATAN RUMBAI KOTA PEKANBARU - Birahmatika, Della; Erlinda, Sri; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the type of socialization for beginner voters as a means to see the beginner voters role in society. The lack of political education the beginner voters got in the Palas District made them did not know about the importance of political participation The formulation of the problem in this research is how is the Type of Political Socialization for Beginner Voters in Palas Rumbai district Pekanbaru City? The purpose of this research is to know the Types of Political Socialization for Beginner Voters in Palas Rumbai district Pekanbaru City. The population of this research is beginner voters in Palas with the numbers of beginner voters are 273 people and the writer tooks 69 people as the samples. The instruments of data collection are observation, questionnaire, interview and documentation. The data collection instrument is a questionnaire consisting of 24 questions and an interview consisted of 24 questions. In analyzing the data, the writer used Qualitative Descriptive analysis. From the results of this study indicated that the types of political socialization for beginner voters in Kelurahan Palas, Rumbai district Pekanbaru, it can be seen from 69 respondents, 52.47% said “yes “ as an answer and 47.53% said “no” to type of direct socialization, while those who answered